2021
DOI: 10.1371/journal.pgen.1009346
|View full text |Cite
|
Sign up to set email alerts
|

Increased dopaminergic neurotransmission results in ethanol dependent sedative behaviors in Caenorhabditis elegans

Abstract: Ethanol is a widely used drug, excessive consumption of which could lead to medical conditions with diverse symptoms. Ethanol abuse causes dysfunction of memory, attention, speech and locomotion across species. Dopamine signaling plays an essential role in ethanol dependent behaviors in animals ranging from C. elegans to humans. We devised an ethanol dependent assay in which mutants in the dopamine autoreceptor, dop-2, displayed a unique sedative locomotory behavior causing the animals to move in circles while… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 108 publications
(163 reference statements)
0
11
0
Order By: Relevance
“…We reasoned that among the genes that are regulated in response to ethanol exposure would be genes that had already been identified as having roles in acute ethanol response phenotypes. We compiled a list of 77 genes that had been confirmed by behavioral testing in our and others’ laboratories to affect ethanol response behaviors in C. elegans 2 , 11 , 31 , 38 49 and compared this list with the set of genes regulated at 480 min of ethanol exposure. We found that 21 of these genes were regulated at 480 min.…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned that among the genes that are regulated in response to ethanol exposure would be genes that had already been identified as having roles in acute ethanol response phenotypes. We compiled a list of 77 genes that had been confirmed by behavioral testing in our and others’ laboratories to affect ethanol response behaviors in C. elegans 2 , 11 , 31 , 38 49 and compared this list with the set of genes regulated at 480 min of ethanol exposure. We found that 21 of these genes were regulated at 480 min.…”
Section: Resultsmentioning
confidence: 99%
“…Although several genes are implicated in addiction behavior, the mechanism by which binge episodes of alcohol consumption lead to addiction, however, remain largely elusive. Caenorhabditis elegans shows sedation and defects in locomotion in response to alcohol at a concentration similar to that seen in humans (Davies et al, 2003;Mitchell et al, 2007;Pandey et al, 2021). Therefore, C. elegans, with a simple nervous system and easy genetic manipulation, serves as a good model system for studying addiction behaviors and their underlying molecular mechanism.…”
Section: Addiction Behaviormentioning
confidence: 97%
“… Body bend and amplitude of a sinusoidal wave during locomotion in C. elegans. The image has been adapted from Pandey et al (2021) . …”
Section: Introductionmentioning
confidence: 99%
“…Increased activity of DAT and tyrosine hydroxylase has also been shown to correlate with D2 auto-receptor activation at saturating levels of ex vivo dopamine in Xenopus oocytes (Mayfield & Zahniser, 2001), and in vitro protein-protein interaction between DAT and the presynaptic D2 auto-receptor has been suggested to facilitate DAT recruitment to the cell surface (Lee et al, 2007). Interestingly, this recruitment tends to decrease in C. elegans mutants deleted in the D2 auto-receptor, upon ethanol exposure (Pandey et al, 2021). Optogenetic and voltammetric studies with rat hypothalamic dopamine neurons in culture suggest that auto-regulatory characteristics of these neurons are attributable to the re-uptake of synaptic dopamine by the dopamine transporter (Stagkourakis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%